Requirements Analysis for a National Bridge Monitoring System - Garita, César (2018)
Bridges represent a fundamental component of the road infrastructure of any country. Damages and deficiencies in bridges can have a direct impact on the execution of socio-economic activities of the general population. In Costa Rica, a complete inventory of bridges on national routes is not yet available, so it is very difficult to know their real condition to design and develop an adequate long-term maintenance and intervention plan, as well as to prioritize the investment of governmental resources. To address this problem, the e-Bridge 3.0 research project at the Technological Institute of Costa Rica, has as its main objective to design a prototype of a bridge monitoring system that allows the integration of information from existing bridge structures in order to support the decision making by various actors and institutions in the area of ​​road management. As a basis for the design of the prototype, a phase of requirements analysis was carried out, including a review of related works and a detailed comparison of existing systems that led to the identification of the actors, information and main processes that should be taken into account for a system of this type. A workshop was also held with a group of potential users of the system to validate the requirements. This article summarizes the results obtained from the analysis of the most important functional requirements for a national bridge monitoring system.